Overcoming drug-resistant lung cancer by paclitaxel-loaded hyaluronic acid-coated liposomes targeted to mitochondria. (2nd December 2018) - Tian, Yongfeng; Zhang, Hua; Qin, Yanmei; Li, Dong; Liu, Yang; Wang, Hao; Gan, Li
Abstract: As a major cause for the inefficiency of cancer chemotherapy, multidrug resistance (MDR) has become a major barrier to cancer treatment. Mitochondrion-orientated transportation of smart liposomes has been developed as a promising strategy to deliver anticancer drugs directly to tumor sites and actively target the mitochondria, so that drugs can interfere with mitochondrial function and facilitate cell apoptosis, overcoming MDR. Herein, we report a novel dual-functional paclitaxel (PTX) liposome system possessing both CD44-targeting and mitochondrial-targeting properties to enhance drug accumulation in mitochondria and trigger apoptosis of drug-resistant cancer cells. Mitochondria-targeting PTX-loaded liposomes were prepared by thin-film hydration and then coated with hyaluronic acid (HA) by electrostatic adsorption. We evaluated the characteristics of the PTX liposomes in vitro, and found that their particle size was about 100 nm and increased to ∼140 nm after modification by HA. The entrapment efficiency was larger than 85%, and stability data indicated that the liposomes were physically and chemically stable for at least one week at 4 °C. We further evaluated the intake, mitochondrial targeting, ATP levels, caspase-3 activity measurement, and antitumor actives of the liposomes. The results indicated that HA-coated liposomes with mitochondria targeting had significant inhibitory effects against A549 and A549/Taxol cells, showing them to be a promising means of improving therapeutic efficacy and overcoming MDR in cancer treatment.